Cell Viability Assay and Surface Morphology Analysis of Carbonated Hydroxyapatite/Honeycomb/Titanium Alloy Coatings for Bone Implant Applications - Sari, Mona; Chotimah, Chotimah; Ana, Ika Dewi; Yusuf, Yusril (MDPI, 2022)
In this work, carbonated hydroxyapatite/titanium alloy (CHA/Ti) and carbonated hydroxyapatite/ honeycomb/titanium alloy (CHA/HCB/Ti) plates were coated using the electrophoretic deposition dip coating (EP2D) method. Analysis of cell viability and surface morphology of CHA/Ti and CHA/HCB/Ti coatings were carried out using the MTT (3-(4,5-Dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide) assay and scanning electron microscopy (SEM), respectively. In a previous study, the thickness and average compressive strength values for the CHA/Ti and CHA/HCB/Ti plates were about 63–89 m and 54–75 MPa, respectively. The result for thickness and compressive strength in this research followed the thickness and compressive strength parameters for coating in bone implants. In this work, the cell viability for incubation times during 24 h and 48 h of CHA/Ti plates is demonstrably superior to that of CHA/HCB/Ti plates, respectively, where the cell viability for CHA/Ti plates increased to ((67 2)%) after incubation for 48 h. According to the one-way analysis of variance (ANOVA), the p-value was <0.05, indicating a significant difference in the average cell viability value across the three groups. Furthermore, the surface of CHA/Ti is not changed after the coating process. These results will yield many positive biomedical applications, especially in bone implants. Overall, CHA/Ti and CHA/HCB/Ti plates can be considered candidates for biomedical applications based on an analysis of surface morphology and cell viability.